Korelasi Antara Sikap Disiplin Siswa Dengan Pencapaian Hasil Belajar Fisika Pada Kelas X Di Sma Negeri 1 Barumun Tengah - Akbar Halomoan Hasibuan; Eni Sumanti Nasution; kasmawati (Universitas Gara Nusantara Padangsidimpuan, 2025)
This study aims to determine the relationship between student discipline attitude and physics learning outcomes in class X at SMA Negeri 1 Barumun Tengah. A quantitative correlational method was applied with a sample of 29 students selected through purposive sampling. Discipline attitude data were collected using a validated 30-item questionnaire with Likert scale 1-4, while learning outcomes were obtained from student report scores. Data analysis included descriptive statistics, normality testing, homogeneity testing, and Pearson Product Moment correlation. The results show that student discipline attitude has an average score of 75.93. Physics learning outcomes fall into the good category, with an average score of 85.48. The correlation analysis revealed a strong and significant positive relationship between student discipline attitude and learning outcomes (r = 0.784; p < 0.05). The coefficient of determination indicates that discipline attitude contributes 61.47% to learning outcomes. This study highlights the essential role of discipline attitude in improving physics achievement in senior high schools.